Effects of innovative finance, strategy, organization and performance: a case study of company - Sönmez Çakır, Fatma; Adıgüzel, Zafer (Emerald Publishing, 2023)
Purpose The aim of the research is to analyze sustainability in energy companies in terms of financial innovation, innovation strategy and organizational innovation. Design/methodology/approach The analysis of this research was done by using the Mplus 7 package program, and the research model was tested using the existing latent variables and their expressions. Data from 298 administrative staff (white collar) working in companies operating in the energy sector were analyzed. Findings Both independent and mediation effects of financial innovation and innovation strategy positively affect sustainability performance. Therefore, it can be concluded that in order for sustainability performance to be positive, importance should be given to financial innovation, innovation strategy and organizational innovation activities. Research limitations/implications As the data were collected from energy companies in this research, it is not correct to generalize the evaluations. Therefore, in terms of the limitations of the research, the sector and sample size should be taken into account in future studies. Originality/value This research conducted in energy companies focuses on the importance of sustainability and has a unique value in the literature as the data is collected and analyzed from white-collar employees.
Keywords: Organizational Innovation Activities (OIA); Financial Innovation (FI); Innovation Strategy (IS); Sustainability Performance (SP)